2023
DOI: 10.1002/adsc.202300228
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed N‐Alkylations of NH‐Sulfoximines Under Visible Light

Abstract: A copper‐catalyzed N‐alkylation of NH‐sulfoximines with alkyl diacyl peroxides under blue light LED irradiation is reported. The process has a good functional group tolerance, and the products are obtained in yields ranging from 45–91%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 61 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…12 Recently, Cu-photocatalyzed N -alkylations of NH-sulfoximines under visible light were realized by Bolm et al (Scheme 1d). 13 Moreover, Pan and Yu's group disclosed a Ru-photocatalyzed decarboxylative alkylation of enamides with alkyl diacyl peroxides under visible-light irradiation (Scheme 1e). 14 It should be noted that transition metal photocatalysts, additives, and conventional organic solvents are still unavoidable in the previously reported photocatalytic systems.…”
Section: Introductionmentioning
confidence: 99%
“…12 Recently, Cu-photocatalyzed N -alkylations of NH-sulfoximines under visible light were realized by Bolm et al (Scheme 1d). 13 Moreover, Pan and Yu's group disclosed a Ru-photocatalyzed decarboxylative alkylation of enamides with alkyl diacyl peroxides under visible-light irradiation (Scheme 1e). 14 It should be noted that transition metal photocatalysts, additives, and conventional organic solvents are still unavoidable in the previously reported photocatalytic systems.…”
Section: Introductionmentioning
confidence: 99%
“…In 2023, the Bolm group demonstrated that in situ generated Cu(I)-NHsulfoximine complexes 104 are photoactive and can react with alkyl diacyl peroxides 102 to synthesize sulfoximines 103, showcasing another application of Cu(I) complexes in synthetic organic chemistry (Scheme 14b). 30 Furthermore, the Nguyen group, reported the diastereoselective C(sp 3 )-O cross-coupling of glycosyl bromides 105 with aliphatic alcohols 106 via photoexcited Cu(I)-alcohol intermediates 108. 31 This protocol realized the efficient synthesis of biologically relevant glycosides 107, highlighting the potential of copper-mediated photochemistry in the synthesis of complex molecules (Scheme 14c).…”
Section: Excited Cu(i)−alkyne-inducedmentioning
confidence: 99%
“…This setup facilitated the enantioselective C–C coupling reaction under visible light excitation, yielding chiral alkyl azoles 99 in good yields with high stereoselectivity (Scheme a). In 2023, the Bolm group demonstrated that in situ generated Cu(I)-NH-sulfoximine complexes 104 are photoactive and can react with alkyl diacyl peroxides 102 to synthesize sulfoximines 103 , showcasing another application of Cu(I) complexes in synthetic organic chemistry (Scheme b) . Furthermore, the Nguyen group, reported the diastereoselective C(sp 3 )-O cross-coupling of glycosyl bromides 105 with aliphatic alcohols 106 via photoexcited Cu(I)-alcohol intermediates 108 .…”
Section: Photoexcitation Of In Situ-generated Cu(i) Complexesmentioning
confidence: 99%
“…Sulfoximines moiety are widely in medicinal and agricultural . As a result, increasing attention has been paid to the synthesis of N -substituted sulfoximine derivatives, and significant progress has been achieved in the field. , Among them, N -sulfenylsulfoximines are one important class of sulfoximines. Traditional approaches for the synthesis of N -sulfenylsulfoximines suffered from the usage of hazardous chloride (Scheme a) .…”
Section: Introductionmentioning
confidence: 99%